(untitled) (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2018)
We have proved in the Battle of nostalgia negative effects that may cause the defeat, as it was in the ranks of the Islamic Army some weak faith, such as some of those who converted to Islam after the conquest of Mecca for fear of connote The cause of their faith Laggard to defeat at the start of the battle, some of them came out in search of booty do not desire to victory nor a request for a certificate The Battle of nostalgia and events revealed to the Prophet (peace be upon him) and his companions how to be a defeat, after being informed of the Messenger of Allah (peace be upon him) that a thing of wonder leak into the hearts of the fighters was too difficult for them Alajtlad in the battle, also saw the Messenger of Allah ( God’s peace be upon him) how the enemy has prepared himself for the fight and wrote the ranks of archers in the fjords and shred in making ambushes while out a lot of young people in the ranks of the Muslim army without a weapon, and alert the Prophet (peace be upon him) factors victory and resolve the fighting, and which manifested itself in the persistence and courage, and a few were around the first two of his companions and supporters